Experimental-Numerical Study of Tensile Strength of the High-Strength Steel S690QL at Elevated Temperatures - Arsić, D.; Djordjević, M.; Zivković, J.; Sedmak, A.; Aleksandrović, S.; Lazić, V.; Rakić, D. (Проблемы прочности, 2016)
We present the experimental-numerical analysis of the influence of temperature on mechanical properties of structural high-strength steel class S690QL. Since the steel S690QL belongs to a group of steels with good mechanical properties, the aim of this paper is to determine the highest temperatures at which these good characteristics are kept. Experimental tensile testings of the specimens were performed at five different temperatures in the range from 20 to 550°C. Beside experimental testing, strengthening curves were calculated and numerical analysis using finite element method was performed. Both the experimental and numerical results have shown that decrease of mecahanical properties occurs at approximately 450°C. Представлены результаты расчетно-экспериментального анализа влияния температуры на механические свойства высокопрочной конструкционной стали S690QL. Определена максимальная температура при статических испытаниях на растяжение, при которой данная сталь сохраняет высокие механические характеристики. Статические испытания на растяжение проводились при пяти различных температурах в диапазоне 20 550°С. Полученные экспериментальные данные сравнивались с результатами конечноэлементных расчетов путем построения соответствующих кривых упрочнения стали. Представлено результати розрахунково-експериментального аналізу впливу температури на механічні властивості високоміцної конструкційної сталі S690QL. Визнаaчено максимальну температуру при статичних випробуваннях на розтяг, за якої ця сталь зберігає високі механічні характеристики. Статичні випробування на розтяг проводились за п'яти різних температур у діапазоні 20 550°С. Отримані експериментальні дані порівнювались з результатами скінченноелементних розрахунків шляхом побудови відповідних кривих зміцнення сталі.